Replication of FLOSS Research as eResearch - Wiggins, Andrea; James Howison; Kevin Crowston (Proceedings of the Oxford e-Research Conference 08, 2008)
We are working to introduce the ideas of eResearch to a multi-disciplinary research domain: those researchers examining Free/Libre and Open Source Software (FLOSS) and its development (Howison, Wiggins, & Crowston, 2008). The first phase of this work focused on building a repository for data on FLOSS teams, FLOSSmole (Howison, Conklin, & Crowston, 2006), and collaborating with other nascent data repositories in the field. Recently we have begun a second phase, which is to introduce another established principle of eResearch, that of broader collaboration through shared workflows accessing these data repositories. To provide an example of the potential value of this principle, we are replicating seminal FLOSS papers using eResearch approaches. This paper describes research outcomes and lessons learned from translating published literature into eResearch workflows.